(3GdWHbGJ GdLdGdjIs - (3LdGd GdOjf eMeO Hf CSYO GdUOjbj GdOhGfj, GdOhGfj,J (B918 (3g` s
(3ChdgG (B:s
(3hUa HeG cGf fYJ ehGgH GhdG hjMJed Ydi JbOjQ Gdfbd HhGSWI s
(3BNQgG (B:s
(3Ch EbGeI GdOdjd Ydi GdJaUjd JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B32s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1069s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs